Early Moral Cultivation to Build and Improve the Character of Millennial Youth - Rilia Agustin; Ishma Amelia (Walidem Institute and Publishing, 2023)
This study aims to 1). Identify sources of morals, concepts, and goals, 2). Understanding the factors of forming morals, 3). Analyze character education from an Islamic perspective and how to implement it. The research method used is a qualitative method with a library research approach with the Koran, hadith, Indonesian translation books, and scientific works, books, and articles that serve as sources of information. The findings of this study indicate that character education has a higher meaning than moral education, therefore character education not only teaches right and wrong, but at the same time instils good habits (habituation) so that students understand, can feel, and are willing to do what is good. Thus, good and bad, according to Islamic morality, are based on the eternal and universal Qur'an and hadiths the fruit of obedience to Allah Ta'ala.